Prayer in Muslim families: A qualitative exploration. Issue 1 (3rd April 2017) - Hatch, Trevan; Alghafli, Zahra; Marks, Loren; Rose, Andrew; Rose, Jennifer; Hardy, Benjamin; Lambert, Nathaniel
ABSTRACT: This qualitative study seeks to examine one major aspect (or "pillar") of Islam, prayer ( salat ). Prayer is a widely practiced religious act; however, a dearth of social science research exists on prayer in relation to Muslim couples and families. The influence of prayer among Muslim couples, marriages, and family life is explored to better inform social work practice in working with American Muslim families. Specifically, we address: (a) prayer during courtship, (b) prayer as a unifying influence in marriage, (c) "a prayer for everything" (even sexual intimacy), and (d) prayer as "the most important foundation" for family relationships. Supportive primary data and social work implications are presented.